Les contrôles américains sur les exportations stratégiques : historique et évolution - Martel, André; Legault, Albert (Études internationales, 1994)
A brief historical survey of the u.s. export controls on strategic goods indicate the importance of the Cold War in achieving these objectives as well as the importance of polycentrism across and within the institutions and agencies concerned. The proliferation of controls has brought about a large area of freedom for the implementation of foreign policy by the executive branch of the Government. After the end of the Cold War, one can surmise that the emphasis mil be felt at three different levels : a greater discretion by national actors in the implementation of export controls policy, a greater harmonization of multilateral efforts designed at promoting the nonproliferation of weapons of mass destruction, and greater cleavages between those who want to relax export controls for economic reasons and those who want to strengthen them for security reasons. On the whole, the multiplicity of legislative actions and organizations concerned can only reinforce the freedom of action of the executive branch of the Government.